Analisis Efisiensi Penggunaan Automatic Tank Gauge (ATG) di Pertamina Berdasarkan Pendekatan Quality, Cost, Delivery, Safety, dan Morale (QCDSM) - Sugara Budiman, Banyu; Prasetya, Dwi Indra; Andriansyah, Agus (Innovative: Journal Of Social Science Research, 2025)
Automatic Tank Gauge (ATG) is an automatic system used to measure levels and monitor fuel stocks in real-time, which aims to improve operational efficiency and accuracy. This study aims to analyze the efficiency of ATG use in Pertamina based on the Quality, Cost, Delivery, Safety, and Morale (QCDSM) approach. This approach is used to evaluate the performance of the ATG system in terms of measurement quality, cost efficiency, delivery timeliness, operational safety, and its impact on employee morale. The research method used is a quantitative approach with data collection through direct observation, interviews, and related document studies. The results of the analysis show that the use of ATG significantly improves the accuracy of fuel stock inventory, reduces operational costs, and increases time efficiency. In addition, the implementation of ATG also has a positive impact on work safety and employee morale by reducing the risk of human error and manual workload.